Análise da regularidade cinemática em corredores com e sem histórico de lesão - Juliana Quirino da Silva (2019)
Running is one of the most popular physical activities. However, several studies have reported a high rate of injuries for runners. Some studies found correlations between injury and several risk factors. However, there is no consensus among researchers about one specific risk factor for running injury etiology. Usually, the classical biomechanics studies used discrete kinematic variables to investigate injury development. These studies considered the linear relationship between kinematic variables and injury to uncover a cause and effect association. Recently, studies have suggested the use of nonlinear methods to investigate the organization of biological system considering the perspective of the complex systems and the relationship with emergence the injuries. The complexity of biological systems can be associated, among other characteristics, with the nonlinear interactions between several independent components responsible for producing human movement. The reduction of the ability to adapt to changes in the imposed task and environmental conditions may indicate changes of the components of the biological system. Considering this, the analysis of the regularity of the running movement pattern is one of the nonlinear measures that can contribute to the understanding of the organization of the system in the task. Therefore, the aim of this study was to investigate the regularity of lower limb joint movements in runners with and without running injury history. A cross-sectional observational design was conducted with nineteen recreational runners with and without injury history. During data collection, subjects ran on a treadmill, at self-selected speed. Lower limb kinematics in the sagittal plane were recorded using an active three-dimensional motion analysis system. The regularity of the kinematic time series of hip, knee and ankle were analyzed by means of sample entropy (SampEn) analysis. Mixed design analysis of variance was performed to investigate the differences between groups. Runners with an injury history had lower SampEn values compared to runners without injury history (P = 0.002). SampEn was higher at the ankle than at the knee (P = 0.001), and at the hip (P < 0.001). SampEn of the knee was greater than at the hip (P = 0.001). The greater regularity of the movement pattern of runners with injury history suggests less adaptability of the neuromusculoskeletal system during the running. In addition, the lower limb joints deal with different demands and the ankle seems to be the most adaptive joint to the perturbations imposed by the environment during the running.